Sex Differences in Aerobic Fitness in Top-Class Soccer Referees. Issue 11 (November 2018) - Castagna, Carlo; Bizzini, Mario; D'Ottavio, Stefano; Araújo Póvoas, Susana C.
Abstract : Abstract: Castagna, C, Bizzini, M, D'Ottavio, S, and Araújo Póvoas, SC. Sex differences in aerobic fitness in top-class soccer referees. J Strength Cond Res 32(11): 3216–3221, 2018—The aim of this study was to assess the aerobic-fitness differences between male and female top-class soccer field referees (FRs). This with the purpose to provide cutoff values useful for training prescription in female FRs. Forty female top-class FRs (age 34.18 ± 3.50 years and 5 ± 3.9 years international refereeing experience) and 52 male FRs (age 38.4 ± 3.3 years and 5 ± 3.5 years international refereeing experience) candidates in the preliminary open list developed by the FIFA Refereeing Department for the 2014 and 2015 World Cup Tournaments, participated in the study. The FRs were tested for aerobic fitness under laboratory conditions with a progressive speed treadmill test until exhaustion. Female FRs showed to possess, on average, lower (large effect) levels of aerobic fitness and performance compared with their male counterparts. The female FRs' V[Combining Dot Above]O2 max (48.1 ± 4.4 ml·kg −1 ·min −1 ) was 7% (large effect) lower than the male FRs (51.9 ml·kg −1 ·min −1 ). Peak treadmill speed was 11% lower (large effect) in female FRs (16.27 ± 0.94 vs. 14.64 ± 0.96 km·h −1 ). The receiver operating characteristic curve analysis enabled cutoff values (47.8 ml·kg −1 ·min −1 for V[Combining Dot Above]O2 max) that may be used as preliminary cues to guide physiological selection and training prescription in female FRs aiming to officiate male-soccer matches. Only 2.5% of the female FRs showed V[Combining Dot Above]O2 max higher than the mean values of male FRs when using the scaled notation (0.68). Female FRs aiming to officiate male competitions should consider training intensities at anaerobic threshold speed (13 km·h −1, 95% heart rate max) when developing aerobic fitness. Given the very large sex differences in aerobic performance, strength/power training should be proposed to perspective female top-class FRs.